ANALYSIS OF FOREIGN INNOVATIVE DEVELOPMENTS IN THE ASSESSMENT AND MITIGATION OF DEBRIS-FLOW AND FLOOD RISKS (Scientific journal of the Fergana State University, 2026)
The article analyzes foreign innovations in protection against debris flows and floods based on key scientific and patent sources from 2010-2024. A shift from traditional infrastructure to integrated systems is identified, which include monitoring, risk-informed design, and flexible modular barriers. Key trends include systemic risk management, data-centricity, probabilistic design, and technological advancement. The necessity of a comprehensive, science-based approach to risk reduction is substantiated.